Formation of Nanotubular TiOa Bioactive Oxide Layer on Titanium and Cell Response Studies by - Sreekantan, Srimala; Ahmad, Zainal Arifin; Mat, Ishak; Mokhtar, Norehan (Universiti Sains Malaysia, 2011)
This work focus on the formation of titanium oxide {Ti02) nanotubes on theTi-6AI-4V alloy by anodization method in organic ethylene giycoi electrolyte (EG). The dimension of nancAubes could betuned by changing the electrochemical parameters such as NH4F content, voltage applied; and anodization time. The average nanoporous or nonotube diameter and length were found to increase with increasing ambunt of fluoride, anodization voltage and anodization time. Minimum of 0.5 g NH4F is required for growth of nanotubes.:TT02 nanotubes with average diameter of 110 nm and 3.1 pm lengths were obtained in EG containing 0.7 g NH4F. Upon annealing from temperature 400°C to 600°C in argon atmosphere shows crystallization of the nanotubes to anatase phase exists at 400°C while rutile dominantly exists at eOO^C. Anodization in the organic electrolyte resulted in homogeneous structure unlike the one reported in aqueous acidified fluoride solution which resulted in inhomogeneous stnjcture due to the severe attack of the p-phase. For the case of behavior of cell interaction using human foreskin fibrobfast cells line (HS27) studies shown that amorphous Ti02 nanotubes structure has better cellular interaction as compare to anatase and rutile crystal structure